Evaluation of Simulation Capability for Multiple Tropical Cyclone Events in the Western North Pacific of the UH_HCM Model - Li, Tianhang; Ren, Hong-Li; Wu, Yujie; Gao, Jianyun (Frontiers in Earth Science, 2021)
The intraseasonal variability of multiple tropical cyclone (MTC) events in the western North Pacific (WNP) during 1979–2015 is analyzed using the best-track dataset archived at the Joint Typhoon Warning Center. MTC events are divided into three phases according to the time intervals of the tropical cyclone (TC) genesis, that is, active, normal, and inactive phases. Composite analysis results indicate that MTC events tend to occur in the active phase when the monsoon trough is stronger and located farther north than at other times. Initialized by the data from a 10-year stable running result, a 12-year control experiment is carried out using the hybrid atmosphere–ocean coupled model developed at the University of Hawaii (UH_HCM model) to evaluate its simulation capability. Compared with the climate observations, the model shows good skill in simulating the large-scale environmental conditions in the WNP, especially the subtropical high and the monsoon trough. In addition, the model can well simulate the climate characteristics of TCs in the WNP, as well as the differences in each MTC phase. However, the simulated frequency of TCs is less and their locations are more northeast, compared with the observations. The vorticity and moisture in the model appear to be the two main factors affecting MTC activity based on analyses of the genesis potential index.